Pro-poor indirect tax reforms, with an application to Mexico - Abdelkrim Araar; Jean-Yves Duclos; Paul Makdissi (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper proposes a methodology for testing for whether tax reforms are pro-poor. This is done by extending stochastic dominance techniques to identify tax reforms that will be deemed absolutely or relatively pro-poor by a wide spectrum of poverty analysts. The statistical properties of the various estimators are also derived in order to make the method implementable using survey data. The methodology is used to assess the pro-poorness of possible reforms to Mexico's indirect tax system. This leads to the identification of several possible pro-poor tax reforms in that country. It also shows how the pro-poorness of a tax reform depends on one's conception of poverty as well as on the revenue and efficiency impact of the reform.
Keywords: D12; D63; H21; I32; 330; Stochastic dominance; pro-poor changes; tax reforms; Mexico